2017
DOI: 10.1159/000475908
|View full text |Cite
|
Sign up to set email alerts
|

Skin-Dominant Phenotype in a Patient with H Syndrome: Identification of a Novel Mutation in the <b><i>SLC29A3</i></b> Gene

Abstract: H syndrome (OMIM 602782) is a very rare autosomal recessive genodermatosis with multisystem involvement. Hallmarks of this disorder are juvenile onset and progressive, hyperpigmented, hypertrichotic lesions with histiocytic infiltration. Associated systemic manifestations form a long list, and there is high variability between patients. In some patients, dysmorphic and other systemic features may be so subtle that the disorder may readily be mistaken as an acquired skin disease and treated as such. Herein, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 14 publications
1
9
0
Order By: Relevance
“…Previous studies have shown that the spectrum of cardiac involvement in H syndrome is widely diversified, including atrial septal defect, ventricular septal defect, mitral valve prolapse, cardiomegaly, left ventricular dilation, pulmonary hypertension, pulmonic stenosis, pericardial effusion, cardiac septal thickening, left superior vena cava, pericarditis, thickening of the posterior pericardium and right atrial wall, bicommissural aortic valve with mild aortic incompetence and acute coronary syndrome . These cardiovascular abnormalities seen in H syndrome patients raise a possible role of hENT3 in normal cardiac activity and morphogenesis …”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Previous studies have shown that the spectrum of cardiac involvement in H syndrome is widely diversified, including atrial septal defect, ventricular septal defect, mitral valve prolapse, cardiomegaly, left ventricular dilation, pulmonary hypertension, pulmonic stenosis, pericardial effusion, cardiac septal thickening, left superior vena cava, pericarditis, thickening of the posterior pericardium and right atrial wall, bicommissural aortic valve with mild aortic incompetence and acute coronary syndrome . These cardiovascular abnormalities seen in H syndrome patients raise a possible role of hENT3 in normal cardiac activity and morphogenesis …”
Section: Discussionmentioning
confidence: 95%
“…19 These cardiovascular abnormalities seen in H syndrome patients raise a possible role of hENT3 in normal cardiac activity and morphogenesis. 19,20 We hypothesize that the expression of mutant hENT3 in the heart could be altered, which probably affects the nucleoside transport activity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…H syndrome (OMIM 602782), first described in 2008 by Molho‐Pessach et al, is a rare, autosomal recessive, multisystem fibrosing histiocytic disorder characterized by hyperpigmentation, hypertrichosis, hepatosplenomegaly, hearing loss, heart abnormalities, hypogonadism, low height (short stature), hyperglycemia, hallux valgus/flexion contractures (camptodactyly), and heritable histiocytosis 4 . Also known as histiocytosis‐lymphadenopathy plus syndrome, it shares features of 3 other histiocytic disorders once thought to be distinct entities: Faisalabad histiocytosis, familial sinus histiocytosis with massive lymphadenopathy (familial Rosai‐Dorfman disease), and pigmented hypertrichosis with insulin‐dependent diabetes mellitus syndrome.…”
Section: Microscopic Findings and Discussionmentioning
confidence: 99%
“…Coincidentally, around the time our work was published, another group investigated a case of H Syndrome that arose from a novel mutation (Glu447Lys) in the SLC29A3 gene. 7 They hypothesized a link between the mutation and the symptoms experienced, ranging from various cardiovascular anomalies to skin-dominant features including hyperpigmentation and hypertrichosis. Our lab's research may hold an explanation for this molecular pathogenesis.…”
mentioning
confidence: 99%